Television as a Source of Information for the Deaf and Hearing Impaired. Captions and Sign Language on Austrian TV - Kurz, Ingrid; Mikulasek, Brigitta (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThe paper sets out to describe the development of services for the deaf and hearing impaired provided by the Austrian Broadcasting Organization (ORF). In 1985, captions were introduced for the prime-time evening news bulletin and for the major news magazines. At present, ORF provides captions for approximately 2,160 program hours annually, giving it a leading position among German-language broadcasting organizations and making 12.5% of the total ORF television output accessible to deaf and hearing-impaired persons. The use of sign language on Austrian television, however, is still fairly limited.